The Influence of Service Quality and Delivery Prices on Customer Satisfaction in Bandar Jaya - Faulina, Ida; Utami Putri, Lisa; F Sanjaya, Vicky (Terbuka Journal of Economics and Business, 2021)
One of the factors that underlie the success and development of shipping service companies is the quality of service and also the shipping rates set by the company. These two factors have a major impact on customer interest and satisfaction in using the delivery service. This study aims to determine whether the quality of service and freight rates affect customer satisfaction. And from the research conducted, it can be concluded that the quality of service and freight rates affect customer satisfaction. This study uses a sample of 50 customers, the data processing method uses the Smart Pls 3 application.